2014
DOI: 10.1007/s11157-014-9343-5
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorus–iron interaction in sediments: can an electrode minimize phosphorus release from sediments?

Abstract: All restoration strategies to mitigate eutrophication depend on the success of phosphorus (P) removal from the water body. Therefore, the inputs from the watershed and from the enriched sediments, that were the sink of most P that has been discharged in the water body, should be controlled. In sediments, iron (hydr)oxides minerals are potent repositories of P and the release of P into the water column may occur upon dissolution of the iron (hydr)oxides mediated by iron reducing bacteria. Several species of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 92 publications
0
15
0
Order By: Relevance
“…Currently, the main application described in the literature for SMFCs is as a long-term power source for autonomous sensors and communication devices [8]. In addition, SMFCs have also been explored as one type of new technology for removing organic matter from sediments [5,9,10] and for controlling phosphorus solubilization in eutrophic lake sediments [11][12][13]. (a), (b), (c), (d), (e) correspond to the points indicated in Figure 2.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, the main application described in the literature for SMFCs is as a long-term power source for autonomous sensors and communication devices [8]. In addition, SMFCs have also been explored as one type of new technology for removing organic matter from sediments [5,9,10] and for controlling phosphorus solubilization in eutrophic lake sediments [11][12][13]. (a), (b), (c), (d), (e) correspond to the points indicated in Figure 2.…”
Section: Introductionmentioning
confidence: 99%
“…As repositories of the overlying water body (e.g., oceans, lakes, rivers, or reservoirs), sediments are usually composed of organic and inorganic materials and shelter a complex microbial ecosystem that thrives on several different electron donors and acceptors12.…”
mentioning
confidence: 99%
“…Microorganisms in sediments mediate several processes in the biogeochemical cycles of carbon, nutrients, metals, and sulfur1. Previous studies also suggested that Microbial Fuel Cells (MFCs) may be used for enhancing biodegradation of contaminants in anoxic environments by providing an inexhaustible source of terminal electron acceptors to a polluted environment89.…”
mentioning
confidence: 99%
“…The electric motor was powered by 12 V DC power source, connected to a shaft which rotated the dialysis tubing holder at 12 rpm for 8 hours a day. Since a metal may function as electron acceptor and promote Fe 3+ reduction in the sediments (Martins et al, 2014), the shaft and the dialysis tubing holder were designed to not contain any metal. The dialysis tubing had a 3,500 MWCO (Fisher).…”
Section: Quantifying P Release From the Sedimentsmentioning
confidence: 99%